Reform of the Stability and Growth Pact: Which changes for the governments? - Séverine Menguy (Journal of Government and Economics)
In 2020, in the context of the COVID-19 health crisis, the rules of the Stability and Growth Pact were temporarily suspended in the European Union. Nevertheless, the European Council and the European Parliament reached an agreement for the reactivation of these rules in 2024. A simple analytical modeling then shows that the empirical implications of the new rules suggested for a reformed Stability and Growth Pact would not be very different from those derived from the rules previously applied. Regarding highly indebted countries, the new debt sustainability safeguard of the reformed SGP could be slightly less binding than the previous rule of the Six Pack requiring to reduce 1/20th of the excess of the public debt each year. However, this criterion as well as those related to the structural budget deficit would not change much the conclusions and the recommendations of the reformed Stability and Growth Pact in comparison with former European fiscal rules. So, reactivated fiscal rules should remain difficult to comply with for many European countries.